2016
DOI: 10.1007/s00421-016-3355-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for measuring energy expenditure of a single sit-to-stand movement

Abstract: This study demonstrated that the EE of an instantaneous movement can be quantified by relating the gross EE and different frequencies of movement. Using this method, we quantified the EE of an STS, which varied depending on participants' anthropometrics. Mets of repetitive STS movement ranged from 2.6 to 7.2. This physiological profile is useful when performing repetitive STS movements as a form of exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
(33 reference statements)
2
13
0
Order By: Relevance
“…No such correlation was observed during the second 5 min of standing. This is in line with recent work regarding the energy cost of sit-stand transitions (Hatamoto et al 2016), which also showed such a correlation, and which is suggested to reflect the larger movement required by individuals of taller stature versus shorter to transition posture from a chair of equal height.…”
Section: Energy Cost Of Standing and Staturesupporting
confidence: 91%
See 3 more Smart Citations
“…No such correlation was observed during the second 5 min of standing. This is in line with recent work regarding the energy cost of sit-stand transitions (Hatamoto et al 2016), which also showed such a correlation, and which is suggested to reflect the larger movement required by individuals of taller stature versus shorter to transition posture from a chair of equal height.…”
Section: Energy Cost Of Standing and Staturesupporting
confidence: 91%
“…This large proportion of people showing standing economy would, a priori, appear to be in conflict with studies reporting significant increases in EE during intermittent standing, instead of prolonged sitting. However, studies showing that breaking up sedentary sitting time with intermittent standing leads to increases in EE (Levine et al 2005) do not distinguish between postural transition and steady-state standing and, thus, it is most likely the transition from sitting to standing (or vice versa) which is increasing EE (Creasy et al 2016;Hatamoto et al 2016;Judice et al 2016) rather than maintaining standing posture per se. Further to this, in the present study we observed a significant correlation between change in EE during the first 5 min of the standing period and height.…”
Section: Energy Cost Of Standing and Staturementioning
confidence: 99%
See 2 more Smart Citations
“…The reasoning for this interest is two-fold: Firstly, breaking sitting time has been shown to decrease metabolic risk independently of moderate-to-vigorous physical activity (Honda et al, 2016), with length of sitting bouts positively correlated with waist circumference and obesity prevalence (Healy et al, 2008; Gupta et al, 2016), and frequent interruptions to sitting time improving postprandial glucose metabolism (Bergouignan et al, 2016), triglyceride levels, waist circumference and BMI (Hamilton et al, 2008; Healy et al, 2008). Secondly, the energy cost of postural transitioning is much higher than that of postural maintenance—with a sit-to-stand transition increasing EE ~35% above sitting metabolic rate (Judice et al, 2016), and showing a positive linear relationship with transition frequency (Hatamoto et al, 2016). Furthermore, the latter study (Hatamoto et al, 2016) demonstrated a four-fold increase in metabolic rate above resting during the performance of sit-to-stand transitions at a rate of 15 per minute, with the exercise still perceived as “light” by the participants.…”
Section: Breaking the Sedentary Thresholdmentioning
confidence: 99%